Adición de orégano (Origanum vulgare L) en el control de Varroa destructor en colmenas de abejas Apis mellifera - Alcívar García, Juleimy Danahí (2025)
The objective of this study was to evaluate the effect of oregano essential oil (Origanum vulgare L.) in controlling varroosis (Varroa destructor) in honeybee (Apis mellifera) colonies. Due to the lack of normality and homogeneity of variance, the non-parametric Kruskal-Wallis test was applied. The tabulated data were analyzed using InfoStat V2.0, 2020. The results showed that Treatment 3 (19.94%) was the most effective, achieving a significant 70% reduction in Varroa destructor infestation. Additionally, this treatment increased the bee population by 30% compared to the control, leading to a 50% increase in honey production, surpassing all other treatments. On the other hand, Treatments 1 (8.42%) and 2 (12.96%) showed positive effects but with lower impact than Treatment 3 (19.94%). These findings highlight oregano essential oil as a natural and sustainable alternative for controlling V. destructor, improving both the health and productivity of bee colonies. It is concluded that oregano essential oil represents a promising option for promoting ecological beekeeping practices and reducing the use of chemical acaricides.